ANALISIS KEPEMILIKAN ASING DAN NILAI PERUSAHAAN NON-KEUANGAN YANG TERDAFTAR DI BEI - Taduga, Felix Kurniawan (JURNAL ILMU MANAJEMEN UNIVERSITAS TADULAKO, 2019)
This study aims to analyse impact of foreign ownership to value of non-financial companies listed on Indonesia Stock Exchange.The independent variables consist of Total Foreign Ownership, Foreign Institution Ownership, and Foreign Company Ownership. The variables control consist of size, age, dummy director. Variable dependent is Company Value, using Tobins'Q ratio. The research sample is 72 companies with purposive sampling sampling technique. Period of data is 5 years, from 2014-2018. Data panel regression using as data analysis method. The results showed that Total Foreign Ownership and Foreign Institution Ownership positively and still significantly at level of <15%. While Foreign Company Ownership has a positive but insignificant relationship to the value company. Size, Age, dummy director is not influence to value company.